Magma storage conditions beneath a peralkaline caldera in the Main Ethiopian Rift - Colby, DJ; Pyle, DM; Fontijn, K; Mather, TA; Nomade, S; Melaku, AA; Mengesha, MA; Yirgu, G (Elsevier, 2024)
The numerous volcanic centres in the Main Ethiopian Rift (MER) present significant but poorly understood hazards to local populations. The MER is also an important site to gain insights into tectonic processes as it captures the transition from continental rifting (to the south) to incipient seafloor spreading (to the north). Peralkaline magmas account for around 90% of the volcanic products found in the MER. Determining the conditions under which these magmas evolve is critical to understanding rift-related volcanism and its associated hazards. Corbetti Caldera has an extensive record of large-scale, predominantly aphyric, peralkaline rhyolite eruptions. However, little is known about the mafic magmas from which these highly differentiated melts have evolved. Here we present data from the only basaltic deposit found within the caldera, coupled with whole rock, glass and mineral analysis of the peralkaline products, to investigate magma storage conditions at Corbetti. We demonstrate that magma mixing played a role in the evolution of the basaltic magmas and use RhyoliteMELTS modelling to show Corbetti's peralkaline magmas likely evolved at pressures between 100 and 250 MPa, from a magma with an initial water content of 0.5–1 wt%, at or below the QFM buffer. Mineral hygrometry on the sparse crystal populations corroborates the RhyoliteMELTS modelling, suggesting that the basaltic magma had 0.1–1.2 ± 0.32 wt% H2O, and the peralkaline magmas an average of ∼5.5 ± 1.25 wt% H2O. These results also match melt inclusion data for Corbetti and other peralkaline systems. We also provide new 40Ar/39Ar ages for two eruptions, a pre-caldera rhyolitic lava flow (206.7 ± 0.9 ka) and a post-caldera peralkaline ignimbrite (160 ± 0.8 ka). These results add to our understanding of the history of Corbetti and the storage conditions of peralkaline magmas within a continental rift setting and highlight the hydrous nature of Corbetti's magmas and the role that H2O plays during explosive eruptions.